The implications of imperfect cash flow management in business - Mohamad Fadzillah, Fazni; Mohd Noor, Azura; Ahmad @ Muhammad, Norizam (Faculty of Accountancy, 2024)
Cash Flow is essentially the inflow and outflow of money from a business. Abdullah et al. (2021) in their study defined 'Cash Flow' as the addition or reduction of cash based on receipt and payment of cash in a business. Moreover, cash flow is the amount of funds received or paid by the organization during the reporting or accounting period. In addition, Lazar (2018) explained that cash flow is the cycle of cash inflows such as sales, cash collected from customers, and investments and cash outflows such as payments for purchases, payments to suppliers, salaries, raw materials, and so on. Cash flow is a vital indication of your business's overall financial strength.